Teaching Experience and Views of Pronunciation Formative Assessment - Qutub, Hassan (International Journal of Linguistics, 2021)
The current study aimed at investigating the differences between novice and expert Arab EFL teachers in their views of providing pronunciation corrective feedback to their students. Four teachers were recruited for the study. Two novice teachers and two experienced teachers. Both groups of teachers were interviewed about their views of providing pronunciation corrective feedback. Interview data analysis revealed the existence of six major differences between novice and experienced teachers in their views of pronunciation corrective feedback. These differences included timing, frequency, considering students’ proficiency level, considering the skill being taught, focus on form and/or meaning, and the range of pronunciation corrective feedback techniques used. Further suggestions included incorporating a pronunciation corrective feedback component in teacher development as well as professional training programs.